Dermatoglifos en dos poblaciones indígenas Guaymí de Costa Rica - Quesada, Misael (1983)
Twenty-three palmar and digital dermatogliphic characters were examined in two Guaymi Amerindian populations, Abrojo and Limoncito, in southeastern Costa Rica. Derrnatogliphs were analyzed in relation to sex, bilaterality or assymetry and differences in pattern frequencies between localities. The sample included 134 males and 127 females in two groups, according to their ethnic and linguistic origin: Western Guaymi (Movere), from Limoncito and Abrojo, and Eastern Guaymi (Murire or Buglere) from Limoncito. When compared with other Amerindian groups, the Guaymi presented a very low finger pattern average, as well a low total ridge count. The Movere subgroup, showed similarities among different patterns both in Limoncito and Abrojo. However there are significant differences between the Murire and Movere groups in relation to the ridge count (ab; bc),atd angle; frequency of designs at the interdigital zone 4; bilaterality; and sex. The results obtained confirm the existence of a marked evolutionary divergence between the two groups.